Application of Chaos in Permanent Magnet Synchronous Motor Optimization - Tan, Pan Long; Song, Yu; Chen, Sha Sha; Gao, Qiang (Applied Mechanics and Materials, 2013)
Permanent magnet synchronous motor (PMSM) is a system with multi-variable, strong coupling and nonlinear. It is difficult to establish its precise mathematical model, and the parameter optimization method of PMSM control system is subject to many limitations. Aiming at the design of PID tuning of PMSM control system, a chaos optimization method based on Logistic chaotic map is proposed to avoid the complex process of PMSM modeling and parameter optimization analysis. Results have shown that this method is simple and efficient with short response time and small overshoot after the parameter optimization.